Reference Values for Handgrip Strength and Their Association with Intrinsic Capacity Domains Among Older Adults - Garcia-Hermoso, A (Wiley Blackwell, 2019)
Objective: The purposes of this study were three-fold: (i) to describe handgrip strength in older individuals aged ≥60 years in Colombia; (ii) to identify sex-specific and age-specific muscle weakness cut-off points in older adults; and (iii) to determine the odds of adverse events for each of the intrinsic capacity domains for individuals with handgrip strength greater than the muscle weakness cut-off points, as compared with their weaker counterparts. Methods: A cross-sectional study was conducted in Colombia, among 5237 older adults aged ≥60 years old (58.5% women, 70.5 ± 7.8 years), according to ‘SABE Survey 2015’. Handgrip strength data were obtained with a Takei dynamometer. Sociodemographic variables, five domains of intrinsic capacity (i.e. locomotion, vitality, cognition, psychological, and sensory), and medical conditions were assessed and analyzed. Adjustments variables were age, ethnicity, socio-economic status, urbanicity, body mass index, smoking status, alcohol intake, drug use, physical activity, and co-morbid chronic diseases. Sex-stratified analyses were conducted with logistic regression models. Results: Handgrip strength was greater among men than among women (26.7 ± 8.5 vs. 16.7 ± 5.7 kg, respectively, P < 0.001) at all ages. Weak handgrip strength cut-off points ranged from 17.4 to 8.6 and from 10.1 to 4.9 in men and women, respectively. Overall, participants with optimal handgrip strength had better intrinsic capacity [in men, odds ratio (OR) = 0.62, 95% confidence interval (CI) 0.53 to 0.71; P < 0.001; and in women, OR = 0.79, 95% CI 0.68 to 0.92; P = 0.002] than their weaker counterparts. Also, men with optimal handgrip strength had a lower risk of hospitalization (OR = 0.47, 95% CI 0.29 to 0.78; P = 0.004) than their weaker counterparts. Conclusions: This study is the first to describe handgrip strength values and cut-off points for muscle weakness among a nationally representative sample of Colombian older adults by age and sex. After categorizing older adults as weak or not weak based on the handgrip cut-off points, non-weakness was associated with a decreased odds of intrinsic capacity impairments. These cut-off points may be good candidates for clinical assessment of risks to physical and mental health in older Colombian adults. © 2019 The Authors. Journal of Cachexia, Sarcopenia and Muscle published by John Wiley & Sons Ltd on behalf of the Society on Sarcopenia, Cachexia and Wasting Disorders